The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/disa.12390
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of post‐disaster social support investigations conducted after disasters that struck the Australia and Oceania continent

Abstract: This scoping review provides a summary of research findings on social support dynamics in the wake of disasters that occurred on the continent of Australia and Oceania between 1983 and 2013. Forty‐one studies, quantitative and qualitative, were summarised, investigating different facets of post‐disaster supportive interactions. All inquiries assessed disasters resulting from natural hazards, with the majority of them conducted following events in Australia and New Zealand. The review revealed similar patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 79 publications
2
30
0
1
Order By: Relevance
“…This is consistent with what others have called compensatory effects of resilience factors (Zimmerman et al, 2013), in which increased levels of resilience factors, although not reducing per se the negative impacts of stressors and risks, have beneficial impacts on wellbeing, thus, in some way compensating for the detrimental effects of stressors and risks. Our findings, mostly highlighting direct effects rather than buffering effects, are also aligned with research on the role of social support in the context of disaster situations, in which many studies have found direct effects while few studies have identified buffering effects (as reviewed by Kaniasty et al, 2020). In the COVID-19 context, from a practice-based perspective, the direct effects of resilience factors suggest that interventions targeting the development of trait resilience, family functioning, social support from friends, social participation, and trust in health institutions may lead to positive impacts that could help counterbalance the negative impacts of the identified risk factors on wellbeing, but that overall, would not directly prevent these negative impacts from happening.…”
Section: Unexpected (Reversed) Buffering Effectssupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with what others have called compensatory effects of resilience factors (Zimmerman et al, 2013), in which increased levels of resilience factors, although not reducing per se the negative impacts of stressors and risks, have beneficial impacts on wellbeing, thus, in some way compensating for the detrimental effects of stressors and risks. Our findings, mostly highlighting direct effects rather than buffering effects, are also aligned with research on the role of social support in the context of disaster situations, in which many studies have found direct effects while few studies have identified buffering effects (as reviewed by Kaniasty et al, 2020). In the COVID-19 context, from a practice-based perspective, the direct effects of resilience factors suggest that interventions targeting the development of trait resilience, family functioning, social support from friends, social participation, and trust in health institutions may lead to positive impacts that could help counterbalance the negative impacts of the identified risk factors on wellbeing, but that overall, would not directly prevent these negative impacts from happening.…”
Section: Unexpected (Reversed) Buffering Effectssupporting
confidence: 84%
“…In studies on trait resilience and similar concepts (e.g., hardiness) as well as social support (Cohen and Wills, 1985;Beasley et al, 2003;Schiff et al, 2010;Kaniasty et al, 2020) an important question that researchers have been asking themselves is: are these factors having direct effects on wellbeing, independently of the levels of exposition to risks and adverse situations, or do they have interactive, buffering effects specifically associated with reduced impacts of stressors and adverse situations on wellbeing and mental health? As indicated above, all of the five considered potential resilience factors emerged as having positive main relationships on at least one of the wellbeing outcomes constructs, providing support to a direct effect model of protective influence.…”
Section: Unexpected (Reversed) Buffering Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global health crises, and large scale disasters more generally, cause families significant stress (1)(2)(3). Reciprocal social support within quality family relationships plays a key role in coping with adversity, and in protecting individual and collective health and well-being during times of heightened stress, such as that imposed by the current coronavirus pandemic (2)(3)(4). During times of crisis, family and community resilience is in part shaped by social processes that reflect prior experiences in close relationships (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Quality family relationships are a well-documented protective factor capable of buffering negative outcomes in the face of adversity (2)(3)(4). The benefits of supportive relationships are observable in a wide range of life domains, and across all stages of the lifecourse (5,6,(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%